Is there a motherhood wage penalty in the Finnish private sector? - Sami Napari (The Research Institute of the Finnish Economy (ETLA), 2007)
Using data from the Finnish private sector, this paper shows that giving birth to a child has negative effects on the mother's wage. Analysis of the reasons for the wage penalty associated with motherhood suggests that the loss of human capital during the child-related career break is an important factor behind the motherhood wage penalty. The paper also finds some evidence that mothers' selection into different types of firms than childless women may contribute to the wage penalty. Instead differences in unobserved time-invariant individual characteristics between mothers and childless women seem to be unimportant in explaining the motherhood wage penalty. Finally, there seems to be variation in the child-penalty across worker and firm characteristics. For example, the penalties are lower in the female-dominated industries than in the male-dominated industries. There is also variation in the motherhood wage penalty across the conditional wage distribution. Most notably, the large average wage penalties for mothers who spend longer periods at home taking care of their children appear to be driven by heavy penalties at the upper tail of the conditional wage distribution.
Keywords: J13; J24; 330; Wages; Mothers; Human Capital; Lohndifferenzierung; Frauenerwerbstätigkeit; Mütter; Privatwirtschaft; Finnland